When Judgments Are Not Enough: Enforcement, Legal Culture, and Substantive Justice in Islamic Family Law - Dewi Oktavia; Imron Rosidi; Sofia Hardani (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
This study examines the effectiveness of post-divorce enforcement of court decisions concerning women’s and children’s rights at the Religious Court of Batam, Indonesia. Using a qualitative field research approach, data were collected between 2023 and 2024 through in-depth interviews with 12 informants (judges, clerks, bailiffs, lawyers, and litigants), analysis of selected court decisions, and procedural observations. While judicial rulings consistently recognize rights to child custody, child support, ʻiddah maintenance, and mutʻah, the findings reveal persistent patterns of non-compliance, including child support arrears, delayed payments, and avoidance of enforcement procedures. These conditions indicate a significant gap between normative recognition and substantive realization of rights. The analysis employs a socio-legal framework of legal system effectiveness, covering legal substance, structure, and culture, and is evaluated through maqāṣid al-sharīʻah, particularly the protection of lineage, property, and life. The findings show that the main problem lies in limited enforcement capacity, reflected in the absence of automatic enforcement mechanisms, institutional constraints, and weak compliance culture. The study argues that realizing maqāṣid al-sharīʻah requires operational enforcement measures, such as automatic wage withholding, administrative integration, and systematic monitoring of maintenance obligations. Without these mechanisms, Islamic family law risks functioning only as symbolic recognition rather than as an effective system of substantive justice and social protection.